Efficacy and safety of first-line treatments for recurrent or metastatic nasopharyngeal carcinoma: a systematic review and network meta-analysis - Cai, Tongze; Lin, Caiyue; Li, Qiongqian; Mo, Juanmei; Zheng, Jinghui; Zhou, Jianlong (Frontiers in Immunology, 2025)
BackgroundTo compare the efficacy and safety of first-line treatments for recurrent or metastatic nasopharyngeal carcinoma (RM-NPC).MethodsWe searched databases, including PubMed, Embase, Cochrane Library, ClinicalTrials.gov, and major international conferences, to identify comparative randomized controlled trials (RCTs) for the first-line treatment of patients with nasopharyngeal carcinoma who have metastasis or recurrence from inception to March 1, 2024. Then, we conducted a Bayesian network meta-analysis and systematic review of RCTs that met the specified inclusion criteria. By calculating the surface under the cumulative ranking curve (SUCRA) for each treatment, we determined their relative advantage: the higher the SUCRA score, the more likely that treatment is to be the optimal choice.ResultsSeven RCTs were included, which involved 1495 patients who received 8 different treatment regimens. Overall, programmed cell death protein 1 (PD-1) inhibitors combined with chemotherapy could be the optimal treatment for patients with RM-NPC. Chemotherapy combined with radiotherapy has a tendency to improve progression-free survival and overall survival. The safety assessment showed no significant difference in the incidence of grade 3 or higher adverse events between any two treatments. Tislelizumab, combined with the standard first-line chemotherapy regimen, appeared to confer the best progression-free survival (SUCRA = 83.16%), overall survival (SUCRA = 83.16%), and objective response rate (SUCRA = 89%).ConclusionsSystematic reviews and network meta-analyses integrate evidence from multiple studies, which enables clinicians to make more informed treatment decisions based on comprehensive comparative efficacy and safety data. For patients with RM-NPC, the combination of tislelizumab and chemotherapy is the optimal first-line treatment.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023491570, identifier CRD42023491570.